Acute-on-Chronic Liver Failure: Etiology of Chronic and Acute Precipitating Factors and Their Effect on Mortality - Gawande, Atul (J Clin Exp Hepatol, 2019)
BACKGROUND: The present study is planned to assess etiologies, course, and outcome in patients with acute-on-chronic liver failure (ACLF). METHODS: Two hundred and eight (182 males and 26 females) patients of ACLF fulfilling modified Asia Pacific Association For Study Of Liver Consensus criteria 2009 admitted to the gastroenterology department of SMS Medical College and hospital, Jaipur, between October 2015 and December 2017 were included. We evaluated etiology of underlying chronic disease and the acute event precipitating decompensation in ACLF. RESULTS: Most common etiology of chronic liver disease (CLD) was alcohol with 133 (63.94 %) patients. Viral hepatitis, cryptogenic cirrhosis, autoimmunity, nonalcoholic steatohepatitis, and Wilson disease as causes of CLD were present in 32 (15.4%), 29 (13.94%), 9 (4.3%), 3 (1.4%), and 2 (1%) cases, respectively. Alcohol, sepsis, bleeding, reactivation of hepatitis B, hepatitis E, antitubercular drugs, and autoimmune hepatitis as the causes of acute event were present in 100 (48.08%), 34 (16.35%), 19 (9.1%), 17 (8.2 %), 15 (7.2%), 13 (6.25%), and 2 (0.96%) patients, respectively. In 8 (3.85%) patients, the precipitating event could not be known. Mortality (in-hospital) in this study was 37.5%. Higher model for end-stage liver disease score and high Child-Turcotte-Pugh score score were significantly associated with mortality (P <0.001). Patients with higher ACLF grade were associated with higher mortality. Alcohol as a cause of CLD was significantly associated with mortality (p=0.0146, 95% confidence interval between 3.802 and 30.979). There was no significant difference regarding acute precipitating events between survivors and nonsurvivors. CONCLUSIONS: Alcohol was the most common cause for chronic etiology as well as acute precipitating event. Alcohol as a cause of CLD was significantly associated with mortality.